Size From Shadow: Some Informational Paths Less Traveled. Issue 1 (2nd January 2016) - Casati, Roberto
ABSTRACT: This article deals with informational structure in cast shadows. Most research on cast shadows has focused on retrieving various geometric properties of the scene from shadow patterns, the shape of objects and distances between objects being the foremost features. Size appears to be a rather neglected aspect. However, shadows contain a wealth of information about size. I explore first a simple heuristic (approximate equivalence of size of shadow and size of object) and some complicating factors: elongated shadows, shadows from pinholes, and penumbra. Finally, I discuss the case of relative size of objects in multiobject scenes with shadows.